Agricultura familiar e redes sociais: uma análise dos trabalhos de marketing digital no Facebook - PUSTILNIK, Graciele dos Prazeres (Universidade Federal do Pará, 2025)
This research investigated the digital marketing strategies used in the Family Farming Fair of Abaetetuba profile on Facebook. The research context was a family farming fair in Abaetetuba, located in the Baixo Tocantins region of Pará, investigating the occurrence of digital marketing present in the “A-Feira Abaeté” profile on Facebook; configuring the search field as the virtual one. The methodology consisted in a Case Study on Facebook. The method used was Netnography with statistical support for processing the data collected from the Facebook profile. Data were collected in 192 posts, the period was from November 2017 to December 2019, classified into 26 categories, after being treated in the SAS statistical program, they were transformed into 4,992 data. The results from the research analysis were presented in tables and graphs, complemented with prints of some profile posts, to highlight the marketing occurrences in the studied categories. The present research demonstrated, as a result, positive and negative aspects in relation to the work to publicize the Fair on the social network. It points out possible strategies on how to better manage marketing on social media. Based on the theoretical concepts, data and research results presented, it is understood that the communication strategies used in "A-Feira Abaeté" were efficient, and that the digital marketing carried out on Facebook promoted product sales, as well as strengthened the farmers as a social group that carries out important work in the city of Abaetetuba. This work enabled greater visibility for the Fairs, pointing out their importance. The research had a social commitment to help groups of farmers who wish to sell their products directly to customers, using social networks as a dissemination channel, benefiting from their low cost.